Kallmann Syndrome and X-linked Ichthyosis Caused by Translocation Between Chromosomes X and Y: A Case Report - H Sait; P Srivastava; P Dabadghao; SR Phadke (JRI, 2021)
Background: Xp22.3 region is characterized by low frequency of interspersed repeats and low GC content. Several clinically important genes including ANOS1 (KAL1) reside in this region. This gene was first identified due to translocation between chromosomes X and Y in a patient with Kallmann syndrome. Case Presentation: A 20 year old male presented with complaints of delayed secondary sexual characteristics, impaired sense of smell, and poor scholastic performance. On examination, he had short stature (151 cm; <3rd centile). His sexual maturity corresponded to Tanner stage 3. Stretched penile length was 3.6 cm (<3rd centile). Right testis was undescended with low left testicular volume (12 ml). There was mild ichthyosis over abdomen and back. He had hyposmia, hoarse voice, and synkinesia. Investigations were suggestive of hypogonadotrophic hypogonadism. Karyotype revealed an extra chromosomal material on p arm of chromosome X (46,Xp+,Y). On cytogenetic microarray, deletion of 8.3 Mb on Xp22.33 region and duplication of 12.8 Mb on Yq11.22 region were identified. The breakpoint on X chromosome resulted in deletion of exons 7-14 of ANOS1 gene and complete STS, NLGN4X, ARSL (ARSE), SHOX, and VCX genes. Conclusion: Patients diagnosed with Kallmann syndrome should receive careful clinical evaluation to detect presence of a contiguous gene syndrome.